2016
DOI: 10.1017/s0021932016000572
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Linear Regression Analysis of Factors Influencing Body Mass Index Among Bangladeshi Married Non-Pregnant Women

Abstract: The aim of this study was to investigate the socioeconomic and demographic factors influencing the body mass index (BMI) of non-pregnant married Bangladeshi women of reproductive age. Secondary (Hierarchy) data from the 2011 Bangladesh Demographic and Health Survey, collected using two-stage stratified cluster sampling, were used. Two-level linear regression analysis was performed to remove the cluster effect of the variables. The mean BMI of married non-pregnant Bangladeshi women was 21.60±3.86 kg/m2, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…28 We found that watching TV as a form of media exposure has a link with underweight status, which coincides with a previous study. 19 We found that women not using oral contraceptives have a higher risk of being underweight, consistent with an earlier study. 28 The study found that total children ever born, family size, and age at first birth were not statistically significant risk factors for underweight, which was a contradictory finding compared with two other studies performed in Bangladesh.…”
Section: Discussionsupporting
confidence: 92%
“…28 We found that watching TV as a form of media exposure has a link with underweight status, which coincides with a previous study. 19 We found that women not using oral contraceptives have a higher risk of being underweight, consistent with an earlier study. 28 The study found that total children ever born, family size, and age at first birth were not statistically significant risk factors for underweight, which was a contradictory finding compared with two other studies performed in Bangladesh.…”
Section: Discussionsupporting
confidence: 92%
“…In our opinion, the use of single level statistical model is not appropriate for analyzing this type of nested dataset [18]. We feel that a multilevel regression models should be preferable, and this model has been used for several other studies that were based on BDHS datasets [9, 17, 28, 29]. In this study, two-level logistic regression models were used to determine the effects of socio-economic, demographic, and behavioral factors with anemia among pre-school children in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Hierarchical linear models are powerful statistical tools and are the preferred method for processing hierarchical data [17]. Before applying the method, the intraclass correlation coefficient (ICC) was used to check the validity of our hierarchical linear model [18]. The ICC measures the degree of correlation among observations within a cluster and ranges between 0 and 1.…”
Section: Hierarchical Linear Modelmentioning
confidence: 99%
“…Multilevel linear regression analysis was conducted using the natural logarithms of the annual total salary and the annual performance salary values as the dependent variables, which can more accurately reflect the distribution of the salaries of medical personnel [19]. The three levels of multiple linear regression model were calculated using [18]…”
Section: Hierarchical Linear Modelmentioning
confidence: 99%